Thermodynamic modeling, synthesis and optimization of extraction - Dehydration processes - Díaz, María Soledad (2000)
The synthesis problem of a new separation operation (dehyextraction) with near critical fluids is formulated as a mixed integer nonlinear programming (MINLP) problem. The key separation properties of the dehyextraction process are predicted by the group contribution with association equation of state (GCA-EOS) that supports property predictions of a rigorous process simulator. The simulator is integrated to a MINLP optimization program. Optimal schemes and operating conditions are determined for different aqueous solutions in a wide range of oxychemical compositions. A detailed study for the recovery and dehydration of ethanol, 2-propanol and acetone and mixtures of these solutes from aqueous solutions using supercritical gases as propane, propylene and isobutane is presented.